2008
DOI: 10.1108/09600030810882825
|View full text |Cite
|
Sign up to set email alerts
|

Logistics capability, logistics outsourcing and firm performance in an e‐commerce market

Abstract: PurposeEffective and efficient supply chain management is critical to the success of firms engaging in e‐commerce. The purpose of this paper is to examine the impact of logistics capability and logistics outsourcing on firm performance in an e‐commerce market environment.Design/methodology/approachThis research examines the relationship between firm's logistics capability, logistics outsourcing and its performance. Multiple‐item constructs are used to measure the strength of logistics capability and firm perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(74 citation statements)
references
References 30 publications
(33 reference statements)
3
43
0
5
Order By: Relevance
“…There are several studies that have investigated logistics outsourcing and firm performance (Cho, Ozment & Sink 2008;Kotabe & Mol 2009;Solakivi et al 2011). However, the actual effect of logistics outsourcing on firm performance remains unknown as there is no consensus among the researchers as to whether the practice leads to improved firm performance (Kotabe & Mol 2009;Lahiri 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies that have investigated logistics outsourcing and firm performance (Cho, Ozment & Sink 2008;Kotabe & Mol 2009;Solakivi et al 2011). However, the actual effect of logistics outsourcing on firm performance remains unknown as there is no consensus among the researchers as to whether the practice leads to improved firm performance (Kotabe & Mol 2009;Lahiri 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have claimed that logistics outsourcing has no effect on firm performance (Hsiao et al 2010;Töyli et al 2008). Cho et al (2008) argued that logistics outsourcing can affect firm performance negatively, whereas Parashkevova (2007) claimed that it results in improved firm performance. Based on the divergent views among researchers, this study highlights that little is known about the relationship between logistics outsourcing and the performance of manufacturing SMEs, specifically in Nairobi.…”
Section: Introductionmentioning
confidence: 99%
“…For e.g. Cho et al (2008) in their empirical explo ration found a positive effect of logistics capability on firm performance. Flynn obtained a positive effect of integrating internal and external operations across the supply chain of a firm on its performance.…”
Section: Supply Chain Innovation and Firm Performancementioning
confidence: 99%
“…Esper et al (2007) categorized logistics capabilities into five broad labels: (a) customer focus capability(also known as demand management interface capability and aims for providing differentiated products and services to customers in a way exceeding their expectations), (b) supply manage ment capability (aimed at reducing the cost of total manu facturing or service generating system, optimal utilization of resources and minimizing total distribution cost), (c) Integration capability (aims to achieve unification of effort among different activities both inside and outside the focal firm), (d) measurement capability (degree to which a firm monitors internal and external operations), and (e) infor mation exchange capabilities (indicates the effectiveness with which a firm collects, stores and distributes tactical and strategic information both internally and externally). Cho et al (2008) empirically examined the relationship between firm's logistics capability, logistics outsourcing and its performance in an ecommerce market environment.…”
Section: Defining Logistics Capabilitiesmentioning
confidence: 99%
“…For this reason, it is appropriate to consider cost as a separate factor from operational performance in this study which the sample was selected in Turkey. in customer position (Cho et al, 2008). So, that relationship is a very important issue for both sides.…”
Section: Research Hypotheses Developmentmentioning
confidence: 99%